On-surface synthesis of a two-dimensional porous coordination network: Unraveling adsorbate interactions - Matena, Manfred; Björk, Jonas; Wahl, Markus; Lee, Tien-Lin; Zegenhagen, Jörg; Gade, Lutz H.; Jung, Thomas A.; Persson, Mats; Stöhr, Meike (Physical review. B, Condensed matter and materials physics, 2014)
We present a detailed experimental and theoretical characterization of the adsorption of the perylene derivative 4,9-diaminoperylene-quinone-3,10-diimine (DPDI) on Cu(111) and compare it to its threefold dehydrogenated derivative 3deh-DPDI, which forms in a surface reaction upon annealing. While DPDI itself does not give rise to long-range ordered structures due to lack of appropriate functional groups, 3deh-DPDI acts as an exoligand in a Cu-coordinated honeycomb network on Cu(111). The main focus of this work lies on the analysis of intermolecular and molecule-substrate interactions by combining results from scanning tunneling microscopy, x-ray photoelectron spectroscopy, x-ray standing wave measurements, and density functional theory. We show, in particular, that the interactions between metal atoms and organic ligands effectively weaken the molecule-surface interactions for 3deh-DPDI leading to an increase in molecule-substrate distances compared to the DPDI precursor. Our experimental findings also shed light on the applicability of current theories, namely van der Waals corrections to density functional theory.
Gesehen am 03.09.2020